ANALISIS KINERJA SISTEM INFORMASI MANAJEMEN DATA TENAGA PENYULUH KB PADA PERWAKILAN BKKBN PROVINSI KALIMANTAN SELATAN - Sari, Dwi Retno; Setiadi, Budi; Rahman, Auliya (Universitas Lambung Mangkurat, 2024)
Data processing for family planning extension workers at the South Borneo Province BKKBN Representative is currently still carried out semi-computer using forms and Microsoft Excel. And document storage still allows for document loss because data processing is still the responsibility of each field assigned to carry out these activities, so that activities often overlap in work units due to data that has not been managed properly. The method used in this research is Waterfall which has 5 stages, namely: Software Requirements Analysis, Software Design, Coding, Software Testing, Software Maintenance. The system testing technique uses the Blackbox technique. In this research, data collection uses direct observation and interview techniques. The modeling used in the process of creating a software development system uses the Unified Modeling Language to describe how the system will run. The programming language used is PHP, and MySQL as database management. With this system, all data and information on the management of family planning extension workers can be linked so that it is faster, more effective and efficient. Keywords: Management Information System, Family Planning Extension Personnel Data, PHP, MySQL